The impact of market innovations on the evolution of norms: The sustainability case - Stephan Müller; Georg von Wangenheim (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
That institutions matter is widely accepted among economists and so are social norms as an important category of informal institutions. Social norms matter in many economic situations, but in particular for markets. The economic literature has studied the interrelation between markets and social norms in both directions - how social norms affect markets and how markets affect social norms. Starting from these two perspectives, we add to the literature, by suggesting a new link between product markets and the evolution of social norms: we analyze how the evolution of a social norm may be affected by a product innovation which adds to the variation of products with respect to their level of norm compliance. We derive necessary and sufficient conditions for a) a positive impact of the innovation on the level of norm adoption and b) for multiplicity of norm equilibria. Finally we discuss policy implications.
Keywords: A13; D02; D11; Q01; Q55; 330; Consumer Behavior; Social Norms; Evolutionary Economics; Sustainability; Innovation